The Study of Multicultural Conflict Resolution Education for Students with a Design Thinking Models Based on Project Based Learning - Aziz, Thoriq Abdul; Maulana, Yana (Pancasila and Civics Education Journal, 2023)
This research is based on a literature analysis of 30 (thirty) relevant journals on the topic of conflict resolution education as part of multicultural education in application and is associated with the development of a project-based learning-based learning design thinking learning model to foster students in civics learning by improving the ability to solve everyday critical-critical problem-based problems in the surrounding environment. The analysis of the journal resulted in two main concepts studied, namely multicultural learning and educational models. development of a design thinking learning model as a way to foster students' critical thinking in learning activities analysing multicultural conflict issues in civic education learning. The analysis method uses systematic literature review by sorting out the selected journals to be discussed and producing the stages of application of the design thinking model to make ideas and reprise the selected work through presentations and independent assessments by teachers as facilitators and developers of learning models. This model aims to prevent the occurrence of potential negative conflicts among students in the future due to increasingly complex social issues.